Tinjauan Hukum Terhadap Tindak Pidana Desersi Anggota TNI: Studi Kasus Ajendam XVIII/Kasuari - Giska Fajari; Nurwidya Kusma Wardhani; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the review of military law for cases of desertion committed by TNI members in the unit. Military law review in criminal cases at Ajendam XVIII/Kasuari in 2018 committed by one of its members. We know that as stipulated in the TNI Law, every member of the TNI has an obligation to submit to official matters. When not complying with these regulations, there will be legal consequences for this. The method of data collection is carried out by means of literacy studies and laws and regulations and conducting qualitative descriptive data analysis to find out how the legal review of criminal cases of desertion of TNI members in a case study at Ajendam XVIII / Kasuari.